Assessing the Effects of Climate Change and Anthropogenic Contributions in Parishan Wetland, Iran - Mohammad Kazemi Garajeh; Khalil Valizadeh Kamran; Bakhtiar Feizizadeh; Omid Ghaffari Aliabad; Mousa Saei; Amin Sadeqi (Land)
Wetlands provide essential benefits, including flood control, water quality enhancement, shoreline erosion prevention, natural resource conservation, recreational opportunities, and esthetic value. However, climate change and human activities have recently posed significant threats to these ecosystems. To address this issue, we employed an integrated approach combining remote sensing and the cloud-free Google Earth Engine (GEE) to monitor the impacts of climate change and human activities on Parishan Wetland in Iran. In this study, various climatic and anthropogenic factors, including air temperature (AT), precipitation, built-up area, croplands, and groundwater storage, were analyzed over the period from 2001 to 2010 to explore their potential effects on wetland conditions. The Pearson correlation test was used to assess the relationships between these variables and wetland health. Also, non-parametric Mann–Kendall (MK) and Pettitt tests were employed to identify monotonic trends and shifts in the time series. The findings suggest a complex interplay of climatic and anthropogenic factors impacting the wetland’s ecosystem. Groundwater availability emerged as the most influential factor, with a very strong positive correlation of 0.92, highlighting the critical role of groundwater in sustaining wetland ecosystems. Air temperature values in recent years have shown a significant increasing trend, while precipitation exhibits a statistically significant decreasing trend. These factors, along with the slightly increasing built-up area, which negatively impacts the natural ecosystem, indicate an urgent need to restore the wetland.